2005
DOI: 10.1017/s0022112004002551
|View full text |Cite
|
Sign up to set email alerts
|

The role of instability waves in predicting jet noise

Abstract: There is a continuing debate about the role of linear instability waves in the prediction of jet noise. Parallel mean flow models, such as the one proposed by Lilley, usually neglect these waves because they cause the solution to become infinite. The result is then non-causal and can, therefore, be quite different from the more realistic causal solution, especially for the chaotic flows being considered here. The present paper solves the relevant acoustic equations for a non-parallel mean flow by using a vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…However, we now have to question the relevance of these conclusions for turbulent jets, as they were based on initially laminar or transitional jets. In fact, the subsequent analytical work of Goldstein & Leib (2005) lends support to the earlier (and present) view of the importance of linear instability waves of the turbulent mean flow field in determining the dominant aft angle sound radiation.…”
Section: Introductionsupporting
confidence: 67%
“…However, we now have to question the relevance of these conclusions for turbulent jets, as they were based on initially laminar or transitional jets. In fact, the subsequent analytical work of Goldstein & Leib (2005) lends support to the earlier (and present) view of the importance of linear instability waves of the turbulent mean flow field in determining the dominant aft angle sound radiation.…”
Section: Introductionsupporting
confidence: 67%
“…However the basic mechanism of this sound source is still subject to discussion. The generation of noise by the rapid growth and decay of instability waves in the jet was for instance proposed and investigated analytically [8,9]. It is interesting to notice that this mechanism is likely to generate a highly directional radiation.…”
Section: Discussion On Sound Sourcesmentioning
confidence: 99%
“…The presence of these two components is supported by the works of Tam et al [2,4] and Viswanathan [6,7] who identified two independent self-similar spectra from a large experimental database of sound spectra. That of a sound source connected to the growing and decaying instability waves is also suggested by analytical works [8,9]. This view of two noise components is attractive, but it suffers from the confusing data available in the literature, whose trends can vary between different experiments because of acoustic contamination [10] or of the use of one-third octave spectra [11].…”
Section: Introductionmentioning
confidence: 96%
“…Such observations have since prompted many attempts at modeling turbulent coherent structures as linear instability modes of the time-averaged flow field -the Kelvin-Helmholtz instability. As examples, we cite the works of Crighton & Gaster (1976), Mankbadi & Liu (1984), Tam & Burton (1984), and Goldstein & Leib (2005). Recent rigorous validations, made possible by the current availability of detailed experimental data and well-validated large-eddy simulation (LES) databases, have leant renewed credence to the linear stability model .…”
Section: Introductionmentioning
confidence: 99%